Mediasi Dalam Penyelesaian Sengketa Proses Pemilu: Pembatasan Kesepakatan Mediasi Yang Tidak Bertentangan Dengan Perundang-Undangan - Jaya, Reki Putera; Rifai, Anis; Suartini, Suartini (JUSTICIA SAINS - Jurnal Ilmu Hukum, 2024)
Mediation becomes a new color in the Election legal system in Indonesia to resolve disputes in the Bawaslu process, in a certain angle dispute resolution through the mediation process in Bawaslu has similarities with the mediation mechanism in the private law framework, but in another angle mediation in Bawaslu becomes part of the public law realm so that in the process of resolving disputes through mediation has limitations that are different from private law. The most striking limitation is regarding the non-caucus provisions in mediation of dispute resolution in the election process where there should be no separate mediation meetings as per the rules applicable in civil law and several other limitations outlined in this study. For this reason, this study can be understood and become material for Bawaslu mediators in resolving election process disputes so that the agreement reached through mediation can be based on law